Homosexuality and the crisis of anglicanism - Sachs, William L. (Cambridge Univ. Press, 2014)
Definitive moment -- The shape of early Christian unity -- When ideals encounter realities -- Reform and the power of the periphery -- Anglican tradition and local prerogative -- The triumph of indigenous Anglicanism -- The rise of Liberalism -- In search of the pure church -- Beyond warring parties